1992
DOI: 10.1007/bf00046046
|View full text |Cite
|
Sign up to set email alerts
|

Partial resistance to neck blast influenced by stage of panicle development and rice genotype

Abstract: Neck nodes of eight rice genotypes were inoculated with a virulent isolate of the blast pathogen at four slightly different, increasingly older stages of panicle development shortly after flowering. Resistance to infection as well as resistance to growth of the pathogen after infection was assessed. Significant differences between genotypes were found for both components of resistance. Resistance to growth of the pathogen sharply increased with aging of the neck node as was indicated by a large reduction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 5 publications
2
7
0
2
Order By: Relevance
“…This range was lower than values found earlier [10], but which corresponded to lesion size at 9 DAI. Incubation periods for neck blast were estimated to 9–10 days [16], and 7–9 days [17], which are close to the results obtained in this study. Lesion lengths on necks ranged between 20 and 30 mm, which are close to the values obtained earlier [17].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This range was lower than values found earlier [10], but which corresponded to lesion size at 9 DAI. Incubation periods for neck blast were estimated to 9–10 days [16], and 7–9 days [17], which are close to the results obtained in this study. Lesion lengths on necks ranged between 20 and 30 mm, which are close to the values obtained earlier [17].…”
Section: Discussionsupporting
confidence: 86%
“…Incubation periods for neck blast were estimated to 9–10 days [16], and 7–9 days [17], which are close to the results obtained in this study. Lesion lengths on necks ranged between 20 and 30 mm, which are close to the values obtained earlier [17]. Sporulation intensity on necks ranged between 25,000 and 40,000 spores per lesion in our study, which corresponds to ranges found at 15 DAI [18] (20,000–80,000 spores per lesion).…”
Section: Discussionsupporting
confidence: 86%
“…Leaf infection reduces the photosynthetic area of the plant, which can lead to its death. Panicle infection is that which causes the most important economic losses via yield reduction (Roumen, 1992).…”
Section: Resumen Evaluación De La Resistencia De Cultivares De Arroz mentioning
confidence: 99%
“…Leaf infection reduces photosynthetic area and may eventually result in plant death. Panicle infection reduces yield and therefore this involves important economic losses (Roumen, 1992).…”
Section: Introductionmentioning
confidence: 99%